Journey of Microfinance in India: Exploring the Historical Context and Impact of Microfinance in India (Journal of Advances and Scholarly Researches in Allied Education, 2017)
The concept of micro credit is not new. It existed in every society in one form or other. Many informal credit groups have been operating in many countries for several years like the susus in Nigeria and Ghana, chit funds and Rotating Savings and Credit Associations (ROSCAs) in India, tontines in West Africa, pasanaku in Bolivia, hui in China etc. It is believed that initially, the informal financial institutions emerged in Nigeria dating back in the fifteenth century.